2018
DOI: 10.1016/j.bjan.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre síndrome de burnout e ansiedade em residentes e anestesiologistas do Distrito Federal

Abstract: There is association between state-anxiety and the emotional exhaustion dimensions of burnout, burnout depersonalization, and trait-anxiety. The occurrence of anxiety can negatively influence the way the individual faces daily stressors, which may be related to the use of ineffective strategies to cope with stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
2
4
0
11
Order By: Relevance
“…Presence of one significantly predicted the occurrence of the others two. Studies done in different settings have found a significant association of burnout with depression [38,46] and anxiety [46] which were consistent with our finding. In the same study [46], anxiety was identified as the significant predictor of depression.…”
Section: Predictors Of Depressionsupporting
confidence: 93%
See 2 more Smart Citations
“…Presence of one significantly predicted the occurrence of the others two. Studies done in different settings have found a significant association of burnout with depression [38,46] and anxiety [46] which were consistent with our finding. In the same study [46], anxiety was identified as the significant predictor of depression.…”
Section: Predictors Of Depressionsupporting
confidence: 93%
“…The first-year residents had significantly higher odds of being burnt out than others. The finding is consistent with a study in which a higher proportion of burnout was seen in first [38,92] and secondyear residents [92]. Another study reported that the second-year residents were less emotionally exhausted and had less psychosomatic symptoms compared to the time when they were in their first year [93].…”
Section: Predictors Of Burnoutsupporting
confidence: 90%
See 1 more Smart Citation
“…Burnout also increases the risk of suicidal ideation [21,31]. Burnout is significantly associated with state-anxiety [32] and depression [33,34]. Neglected burnout also results in other serious consequences such as substance abuse, depression, insomnia and, impaired interpersonal and marital relationship [35].…”
Section: Introductionmentioning
confidence: 99%
“…Muitos dos artigos selecionados relataram a necessidade de um suporte adequado na própria instituição de atuação como apoio para o profissional de modo a prevenir a síndrome de Burnout ou para o auxiliar na recuperação [2,8,12,17,19,24]. Dentre as propostas estão: maior acompanhamento do preceptor para com o residente de modo a orientar adequadamente nos procedimentos auxiliando nas dúvidas e dificuldades; reuniões mensais entre os residentes para discussão desse fator que cada vez mais tem afetado a classe médica, principalmente os recémformados; padronizar as horas de estágio evitando longas jornadas por semana; criação de programa de treinamento dedicado à resiliência e habilidades de enfrentamento; otimizar um ambiente respeitoso de trabalho; além do incentivo aos residentes a frequentarem tais grupos de apoio (Tabela 2).…”
Section: Discussionunclassified